The Role of Big Data Predictive Analytics as A Mediator of The Influence of Recruitment and Selection, Remuneration and Rewards, Training, and Development on Employee Retention - Hilman Masputra; B. Medina Nilasari; M Nisfiannoor (PT. Publikasiku Academic Solution, 2023)
The purpose of this study was to determine the effect of recruitment and selection, remuneration and rewards, as well as training and development on employee retention mediated by the big data predictive analytics variable. The method in this study uses a quantitative method which is an approach, an assessment based on numbers using statistical calculations. The samples in this study were employees of PT Addis Citra with a total of 145 respondents. The data collection technique used in this study was a questionnaire or questionnaire. While the data analysis in this study used the Structural Equation Model (SEM) with the AMOS 26 program. The research results obtained show that the variables of recruitment and selection, remuneration and rewards, and training and development have an effect on big data predictive analytics. Furthermore, big data predictive analytics variables affect employee retention, and big data predictive analytics has a mediating role in influencing recruitment and selection, remuneration and rewards as well as training and development on employee retention.